Overweight/obesity and chronic health conditions in older people with intellectual disability in Ireland. Issue 12 (9th November 2021) - Ryan, J.; McCallion, P.; McCarron, M.; Luus, R.; Burke, E. A.
Abstract: Background: This study examines overweight/obesity and chronic health conditions (CHCs) in older people with intellectual disability (ID). Methods: Data for this cross‐sectional observational study emanated from Wave 2 of the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing, a longitudinal study assessing the health and well‐being of older Irish adults with ID aged ≥40 years across all levels of ID. Participation involves an interview process and collation of objective health measures. In this study, body mass index (BMI) ( n = 572), used as a measure of weight status, was examined with clustered doctor's diagnosed CHCs. Descriptive analysis was conducted where counts ( n ) and proportions (%) were used to summarise the variables univariately, while cross‐tabulations were used for bivariate summary into counts and proportions. With overweight/obesity prevalence established and patterns described using logistical regression, Pearson's chi‐squared test was used to test for significant associations. Results: Overweight/obesity identified in 69% of participants occurred with greater frequency in women (72%). A higher percentage of participants aged <50 years (72.5%) were overweight/obese than those aged 50–64 (70%) and 65+ (61.4%). Level of ID and residence type were significantly associated with weight status ( P < 0.001), with overweight/obesity more prevalent in mild (85.7%) than moderate (72%) or severe/profound ID (51.4%). Of those who lived independently/with family, 78.4% were overweight/obese, as were 74% living in a community group home ( P < 0.001). Almost all overweight/obese participants' waist measurements were in the substantially increased risk of metabolic disease waist measurement category (92%, P < 0.001). Logistical regression used to model CHCs on BMI showed significant association between BMI and gastrointestinal tract [odds ratio (OR) = 0.57, P < 0.008, 95% confidence interval (CI) = (0.37; 0.86)], respiratory condition [OR = 8.95, P < 0.004, 95% CI = (2.57; 56.72)] and musculoskeletal disorders [OR = 0.40, P < 0.001, 95% CI = (0.25; 0.63)]. Conclusions: The findings illustrate the strong cross‐sectional association between overweight/obesity and CHCs. These findings suggest a need to prioritise weight status as a health risk to people with ID as they age.